STUDI TENTANG KERUSAKAN HUTAN DI KENAGARIAN KOTO NAN TIGO UTARA SURANTIH KECAMATAN SUTERA KABUPATEN PESISIR SELATAN - Adelinawati, Riri; Juita, S.Pd. M.Si, Erna; Zuriyani, M.Si, Elvi (Pendidikan Geografi, 2014)
Abstract This research aims to get the data, process, analyze and discuss on: 1) factors of destruction of forests in Northern in Kenagarian Koto Nan Tigo Utara Surantih Sub district Sutera Pesisir selatan district 2) impact damage to forests on the environment in Kenagarian Koto Nan Tigo Utara Surantih Sub district Sutera Pesisir Selatan district, 3) countermeasure of forest damage in Kenagarian Koto Nan Tigo Utara Surantih sub district Sutera Pesisir Selatan district. Type of this research is Descriptive research. The population of this research is the whole community around the forest in Kenagarian Koto Nan Tigo Utara Surantih sub district Sutera Pesisir Selatan district. The research sample is taken, with proportional random sampling techniques, with sample on tenis reaserch of 103 people. Data collection using question form of misguided social interactions, analysis used are descriptive statistics using the formula percentages. Results of the study include: 1) cause damage to forests in the Northern in Kenagarian Koto Nan Tigo Utara Surantih Subdistrict of people activities in the forest. The community makes use of the forest as a livelihood because no other work (50,49%) 2). impact of forest damage on the environment including the occurrence of floods (72,82%). 3) countermeasure of forest damage during processing by doing a forest reforestation (56,31%), reduce deforestation (66,99%).